Effect of a postpartum family planning intervention on postpartum intrauterine device counseling and choice: evidence from a cluster-randomized trial in Tanzania - Erin Pearson; Leigh Senderowicz; Elina Pradhan; Joel Francis; Projestine Muganyizi; Iqbal Shah; David Canning; Mahesh Karra; Nzovu Ulenga; Till Bärnighausen (BMC, 2020)
Abstract Background The World Health Organization recommends postpartum family planning (PPFP) for healthy birth spacing. This study is an evaluation of an intervention that sought to improve women's access to PPFP in Tanzania. The intervention included counseling on PPFP during antenatal and delivery care and introducing postpartum intrauterine device (PPIUD) insertion as an integrated part of delivery services for women electing PPIUD in the immediate postpartum period. Methods This cluster-randomized controlled trial recruited 15,264 postpartum Tanzanian women aged 18 or older who delivered in one of five study hospitals between January and September 2016. We present the effectiveness of the intervention using a difference-in-differences approach to compare outcomes, receipt of PPIUD counseling and choice of PPIUD after delivery, between the pre- and post-intervention period in the treatment and control group. We also present an intervention adherence-adjusted analysis using an instrumental variables estimation. Results We estimate linear probability models to obtain effect sizes in percentage points (pp). The intervention increased PPIUD counseling by 19.8 pp (95% CI: 9.1 - 22.6 pp) and choice of PPIUD by 6.3 pp (95% CI: 2.3 - 8.0 pp). The adherence-adjusted estimates demonstrate that if all women had been counseled, we would have observed a 31.6 pp increase in choice of PPIUD (95% CI: 24.3 - 35.8 pp). Among women counseled, determinants of choosing PPIUD included receiving an informational leaflet during counseling and being counseled after admission for delivery services. Conclusions The intervention modestly increased the rate of PPIUD counseling and choice of PPIUD, primarily due to low coverage of PPIUD counseling among women delivering in study facilities. With universal PPIUD counseling, large increases in choice of PPIUD would have been observed. Giving women informational materials on PPIUD and counseling after admission for delivery are likely to increase the proportion of women choosing PPIUD. Trial registration Registered with clinicaltrials.gov ( NCT02718222 ) on March 24, 2016, retrospectively registered.